Sistem dan Prosedur Pemberian Kredit di KSP Nasari KC Medan - Ripho Delzy Perkasa; Ary Sahputra; Nisa Nisa; Damaiyanti Tambunan (CV. ULIL ALBAB CORP, 2024)
This research aims to analyze the credit granting system and procedures at KSP Nasari KC. Medan. The research method employed includes interviews with KSP managers, documentary studies, field observations, literature reviews, and distribution of questionnaires to customers or potential customers. The results of the research indicate that KSP Nasari KC. Medan has a credit granting system and procedures that have implemented various assessment aspects, such as character, capacity, capital, collateral, and economic conditions. This research also identifies strengths and potential areas for improvement in the system and procedures. Based on the analysis, it is concluded that KSP Nasari KC. Medan has a fairly good credit granting procedure, although there are several areas that can be improved to enhance effectiveness and efficiency in granting credit to its customers.